Environmental engineering - Peavy, Howard S.; Rowe, Donald R.; Tchobanoglous, George (McGraw-Hill series in water resources and environmental engineering, 1985)
Brings together and integrates the three principal areas of environmental engineering - water, air, and solid waste management. This title introduces an approach by emphasizing the relationship between the principles observed in natural purification processes and those employed in engineered systems. It offers illustrations and problems